Competências de liderança em pesquisa de clima organizacional: um estudo de caso em empresa do segmento hospitalar - Ornellas, Antonio José Macha (2008)
This work was aimed at analyzing, through the application of a case study, the leadership competences in an Organizational climate survey, with the perception of a hospital segment company s employees in the years of 2004, 2006 and 2008. From this objective, a study was done about the evolution of these leadership competences perceptions during this period of time. To accomplish this study, two sets of hypotheses were proposed, such as: 1) In the results of the Organizational Climate Survey must be present the perception related with the leadership competences; 2) The leadership competences may influence in the results of the Organizational Climate Survey. In order to develop the study proposed here, the methodology included qualitative and quantitative tools. First, it was applied an instrument- a questionnaire for all company s employees during the years of 2004,2006 and 2008. After, one interview was conducted with the company s Human Resources and Climate Survey Responsible. The data collected were treated using the frequency distribution analysis method, with support given by PUC/SP. The results showed that the leadership competences may influence the Organizational Climate Survey